Lime equivalence values of 19 biochar products made from defatted cottonseed meal, poultry litter, and woody sources for quality assessment - Olaniyi Adewumi; Zhongqi He; Renuka Dhandapani; Mingxin Guo (Agricultural & Environmental Letters)
Abstract The lime equivalence, expressed in calcium carbonate equivalent (CCE), is an important quality parameter of biochar as a soil amendment. This work measured the CCE values and the relevant physicochemical parameters of seven defatted cottonseed meal‐, seven poultry litter‐, and five wood‐based biochar products. The CCE of the 19 biochar samples covered a wide range of values from 2.75 to 128.0 g CaCO3 kg−1. Furthermore, the lime equivalence showed a significant (p < 0.05) correlation with the pH parameter, but not (p > 0.05) with the organic content, ash content, electrical conductivity, and sum of soluble base cations. As biochar products with greater lime equivalence have the advantages to substantially reduce soil acidity and improve soil fertility, information derived from this work would shed light on biochar product optimization and appraisals for preferably rectifying strongly acidic soils via efficiently neutralizing soil acids, raising soil pH, and enhancing soil health and productivity. Core Ideas Lime equivalence values and relevant parameters of 19 agricultural and forest byproduct biochar samples were measured. The measured lime equivalence of biochar covered a wide range from 2.8 to 128.0 g CaCO3 per kg of mass. The lime equivalence of biochar samples shows meaningful (p < 0.05) correlation with pH parameter. Total soluble base cations show significant (p < 0.05) correlations with the electrical conductivity and ash content.